Physical and Biological Factors Underlying Long-Term Decline of Dissolved Oxygen Concentrationin the East/Japan Sea - Kim, Haejin; Hirose, Naoki; Takayama, Katsumi (Frontiers in Marine Science, 2022)
A substantial decrease in the dissolved oxygen (DO) concentration over the lower layers of the East/Japan Sea (EJS), including the deep and bottom waters (1500 to 2500 m and 2500 to 3500 m, respectively), has been reported during the last few decades. This study quantitatively explain the mechanisms underlying the long-term decline in the DO concentration of the EJS for the first time using a coupled physical-biogeochemical model. We demonstrated that the cessation of new water formation was a major factor underlying the long-term decline in the DO concentration over the lower layers, and its contribution exceeded the net decrease. In addition, our simulations confirmed that the enhanced primary production in the euphotic zone accompanying increases in organic matter exported to the lower layers accelerates the DO decline in a quantitative respect. It was accounted for 12% of the net DO change at the lower layers from 1980 to 2015. The enhanced primary production resulted from increases in available nutrients due to the intensified vertical mixing caused by the strengthened inflow transport through the Korea/Tsushima Strait. Physical activities such as vertical transport of oxygen from the central water increased the DO concentration of the lower layers, and offset 42% of the net decrease in DO concentration due to organic matter decomposition.